Analysis of the Effect of Magnetic Field on Solidification of Stainless Steel in Laser Surface Processing and Additive Manufacturing - Svetlana A. Gruzd; Stepan L. Lomaev; Nikolay N. Simakov; Georgii A. Gordeev; Anton S. Bychkov; Artem A. Gapeev; Elena B. Cherepetskaya; Mikhail D. Krivilyov; Ivan A. Ivanov (Metals, 2022)
The problem of surface processing and microstructure refinement in stainless steels in laser surface processing in the presence of an external magnetic field has been studied experimentally and theoretically. The effect of both alternating and permanent magnetic fields is discussed. The experimental part includes microstructure assessment of a thin stainless plate annealed by a quasi-continuous laser in the presence of an electromagnetic acoustic transducer. Complementary analytical calculus and numerical simulations of complex transport phenomena in the melting zone are performed. Based on the received data, the effect of the electromagnetic field on the molten zone under laser melting conditions is evaluated and quantified. The obtained results are relevant to laser surface hardening and additive manufacturing.